Brainstem Application of Melanocortin Receptor Ligands Produces Long-Lasting Effects on Feeding and Body Weight - Grill, Harvey J. (J Neurosci, 1998)
Recent evidence suggests that the central melanocortin (MC) system is a prominent contributor to food intake and body weight control. MC receptor (MC-R) populations in the arcuate and paraventricular nuclei are considered probable sites of action mediating the orexigenic effects of systemically or intracerebroventricularly administered ligands. Yet, the highest MC4-R density in the brain is found in the dorsal motor nucleus of the vagus nerve, situated subjacent to the commissural nucleus of the solitary tract, a site of pro-opiomelanocortin mRNA expression. We evaluated the contribution of the caudal brainstem MC system by (1) performing respective dose–response analyses for an MC-R agonist (MTII) and antagonist (SHU9119) delivered to the fourth ventricle, (2) comparing, in the same rats, the fourth intracerebroventricular dose–response profiles to those obtained with lateral intracerebroventricular delivery, and (3) delivering an effective dose of MTII or SHU9119 to rats before a 24 hr period of food deprivation. Fourth intracerebroventricular agonist treatment yielded a dose-dependent reduction of short-term (2 and 4 hr) and longer-term (24 hr) food intake and body weight. Fourth intracerebroventricular antagonist treatment produced the opposite pattern of results: dose-related increases in food intake and corresponding increases in body weight change for the 24–96 hr observation period. Comparable dose–response functions for food intake and body weight were observed when these compounds were delivered to the lateral ventricle. Results from deprived rats (no effect of MTII or SHU9119 on weight loss) support the impression derived from the dose–response analyses that the body weight change that follows MC treatments is secondary to their respective effects on food intake. Results support the relevance of the brainstem MC-R complement to the control of feeding.